2010
DOI: 10.1016/j.febslet.2010.11.045
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum neurotoxin subtype A2 enters neuronal cells faster than subtype A1

Abstract: Edited by Maurice Montal Keywords:Botulinum neurotoxin BoNT/A1 BoNT/A2 Cell based assay Cell entry Neuron a b s t r a c t Botulinum neurotoxins (BoNTs), the causative agent of human botulism, are the most potent naturally occurring toxins known. BoNT/A1, the most studied BoNT, is also used as an important biopharmaceutical. In this study, the biological activity of BoNT/A1 is compared to that of BoNT/A2 using neuronal cell models. The data obtained indicate faster and increased intoxication of neuronal cells b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
79
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 48 publications
9
79
0
1
Order By: Relevance
“…These results indicate A2 has comparatively greater activity in neuronal cell models than in the in vivo mouse bioassay. However, we indicated in a previous report an EC 50 of ϳ0.1 U for A2 in RSC cells, which was only about 2-fold lower than that for A1 (20). While we presently cannot explain this difference, it is interesting that the specific activity in mice of the previous A2 stock was over 3-fold lower than that tested here (4.3 ϫ 10 8 U/mg versus 1.27 ϫ 10 8 U/mg) and that the molar activities of A2 in cells in the two studies were therefore similar.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These results indicate A2 has comparatively greater activity in neuronal cell models than in the in vivo mouse bioassay. However, we indicated in a previous report an EC 50 of ϳ0.1 U for A2 in RSC cells, which was only about 2-fold lower than that for A1 (20). While we presently cannot explain this difference, it is interesting that the specific activity in mice of the previous A2 stock was over 3-fold lower than that tested here (4.3 ϫ 10 8 U/mg versus 1.27 ϫ 10 8 U/mg) and that the molar activities of A2 in cells in the two studies were therefore similar.…”
Section: Discussionmentioning
confidence: 93%
“…It remains unclear how these amino acid differences affect the subtypes' biologic activity, and only a few differences in characteristics have been elucidated. BoNT/A2 has been shown to enter cells faster than BoNT/A1 (20), to more potently inhibit the grip strength in rats after local administration, and to be more potent in the hemidiaphragm assay (21,22). In addition, grip strength analysis after local injection in rats indicated that BoNT/A2 diffusion to the contralateral leg was reduced nearly 3-fold compared to A1 diffusion and no axonal transport was observed (21).…”
mentioning
confidence: 90%
“…BoNT/A1 and BoNT/A2 possess similar potencies but have unique rates of entry into neurons and unique pathologies in mouse models of botulism (28). The current study resolved the sequential entry of H C A1 and H C A2 entry into neurons, identifying an initial ganglioside-dependent step and a subsequent step involving association with synaptic vesicles.…”
Section: Discussionmentioning
confidence: 94%
“…For example, BoNT/A1 appears to be more potent than BoNT/A2 for grip strength on the contralateral side (27), and BoNT/A1 shows more contralateral spread than BoNT/A2, which is prevented by colchicine treatment in a rat model (26,27). In addition, BoNT/A2 is more potent than BoNT/A1 in cultured primary neurons (24,28). Retrograde movement of BoNT/A1 has been observed in mice (29)(30)(31) and cultured neurons (32), but BoNT/A2 trafficking has not been examined.…”
mentioning
confidence: 99%
“…Very soon after the elucidation of the endopeptidase activity of BoNT toward SNARE proteins, immuno blots of toxin-treated synaptosomes or neuronal cells were probed with anti-SNAP-25 or anti-VAMP antibodies to visualize the substrate cleavage (Poulain et al 1993;Schiavo et al 1993). Twenty years later, this is still a useful technique in the field of basic research, e.g., to study cellular uptake kinetics (Pier et al 2011). This type of endopeptidase assay is particularly useful for deducing BoNT activity by analyzing cell lysates for SNARE cleavage, e.g., to show the persistence of BoNT activity ex vivo or to demonstrate the anterograde axonal transport and transcytosis of catalytically active BoNT/A (Keller et al 1999a;Restani et al 2011).…”
Section: Endopeptidase Assaysmentioning
confidence: 99%